An investigation of the relationship between Service Quality and Customer Satisfaction in Melaka Bookstore - Rashid, N.A.; Hamid, A.K.A.; Said, N.; Musa, H. (International Journal of Human and Technology Interaction (IJHaTI), 2020)
Customer satisfaction is a significant factor in influencing the service sector’s revenue. In this competitive environment which full of advance technologies, delivering a high quality of service is a factor for a stable competitive advantage. Customer satisfaction has a beneficial impact on the profitability of an organization. Service quality will reflect the customer’s satisfaction in dimension of tangibles, reliability, assurances, empathy and responsiveness. Although there are many researches about SERVQUAL Model, but there are not much academic evidence measuring customer satisfaction in the bookstore services. Therefore, this research attempts to describe the relationship of service quality and customer satisfaction in the business-to-consumer (B2C). Business to Consumer or B2C is used by businesses that intend to market the products or services to consumers. B2C will conduct directly that business with customers without middleman. Data collection covers 15 bookstores in Melaka state. This research will focusing on selected bookstores such as Popular bookstore, MPH bookstore, TS Commerce bookstore, Kedai Buku Pintar Sdn Bhd and other bookstores that situated in the area of Melaka Tengah. The 151 survey questionnaires received and analyzed using SPSS software. Based on the regression analysis, onlytwo variables from five variables are significant. The two significant variables are reliability and empathy but have positive relationship with customer satisfaction.